Titanium Dioxide (TiO2) Modified Bentonite for Photodegradation in Methylene Blue Dye - Sri Hilma Siregar; Prasetya Prasetya; Norramizawati Norramizawati; Marlian Marlian; Aulia Rizki Ramadhanti (Jurnal Kimia Sains dan Aplikasi, 2023)
Dye is one of the waste waters, which will be a problem if the content is excessive in the water. Modifying bentonite with titanium dioxide (TiO2) as a photocatalyst for removal of dye waste. In this study, composite synthesis was carried out by mixing bentonite and TiO2 suspensions. The mass of bentonite is 20 g, and the mass variations of TiO2 are 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. The resulting composite was heated using a furnace at 550°C for 5 hours. Bentonite-TiO2 composites were characterized using Fourier Transform Infrared, X-Ray Diffraction, and Scanning Electron Microscope-Energy Dispersive X-Ray (SEM-EDX). Photodegradation of methylene blue dye with bentonite-TiO2 was carried out by varying the mass of bentonite-TiO2 photocatalysts (0.02, 0.04, 0.06, 0.08 g); variations in pH (1, 3, 5, 7, and 9), and variations in UV irradiation time (30, 60, 90, and 120 minutes). The results of characterization with FTIR showed the presence of Ti-O-Ti vibrations at wavenumber 1419 cm-1 and Si-O-Ti at wave numbers 780 cm-1 and 799 cm-1. Characterization of 20% bentonite-TiO2 by XRD showed rutile, anatase, and montmorillonite phases. The SEM-EDX bentonite-TiO2 characterization results produced some small particles with a layered structure with TiO2 particles clumping and still in the form of agglomerates, and the EDX results showed the chemical composition of Si and Ti. The results of photodegradation showed that the best activity for the bentonite-TiO2 composite occurred in photocatalyst BT-20% with a mass of 0.08 g, pH 1, and UV irradiation time of 120 minutes with methylene blue 99.942% degraded.